Hi there! Thank you for the opportunity to help you with your question!

When f is written as f(x) = mx + b, then m is the slope of the function and b is the y-intercept. We are given that the slope is -1, so m = -1. Replacing that we have that:

f(x) = -x + b

Now, in order to find b we need to use the information that f(1) = 2. We do that by letting x= 1:

f(1) = 2 = -1 + b

b = 3

Therefore, the equation of the line is:

f(x) = -x + 3, so m=-1, b =3

Please let me know if you need any clarification. Always glad to help!